1998
DOI: 10.1099/00207713-48-1-107
|View full text |Cite
|
Sign up to set email alerts
|

PCR fingerprinting of whole genomes: the spacers between the 16S and 23S rRNA genes and of intergenic tRNA gene regions reveal a different intraspecific genomic variability of Bacillus cereus and Bacillus licheniformis

Abstract: Genomic diversity in 21 strains of Bacillus cereus and 10 strains of Bacillus licheniformis was investigated by random amplified polymorphic DNA (RAPD) analysis, which samples the whole genome, and by two PCR fingerprinting techniques sampling the hypervariable spacers between the conserved 165 and 235 rRNA genes of the rRNA gene operon (ITS-PCR) and regions between tRNA genes (tDNA-PCR). RAPD analysis showed a remarkable diversity among strains of B. cereus that was not observed with the rRNA and tRNA interge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(51 citation statements)
references
References 42 publications
2
48
0
1
Order By: Relevance
“…Among the molecular techniques for the soil bacterial community analysis AR-ISA proved to be very effective. The ARISA (Fisher and Triplett, 1999) is a PCR-based fingerprinting approach targeting the 16S-23S intergenic transcribed spacers a region considered hypervariable respect to the adjacent genes and hence useful to discriminate bacteria at the subspecies level (Daffonchio et al, 1998(Daffonchio et al, , 2000. The advantage of ARISA respect to the traditional analysis of fingerprinting patterns in agarose/polyacrylamide gels is the separation of labelled fragments in an automated sequencer which guarantees high sensitivity also for poorly amplified fragments and high resolution even of hundreds of peaks per profile (Ranjard et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the molecular techniques for the soil bacterial community analysis AR-ISA proved to be very effective. The ARISA (Fisher and Triplett, 1999) is a PCR-based fingerprinting approach targeting the 16S-23S intergenic transcribed spacers a region considered hypervariable respect to the adjacent genes and hence useful to discriminate bacteria at the subspecies level (Daffonchio et al, 1998(Daffonchio et al, , 2000. The advantage of ARISA respect to the traditional analysis of fingerprinting patterns in agarose/polyacrylamide gels is the separation of labelled fragments in an automated sequencer which guarantees high sensitivity also for poorly amplified fragments and high resolution even of hundreds of peaks per profile (Ranjard et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For the ARISA experiments (Fisher and Triplett, 1999), the intergenic transcribed spacers (ITS) between 16S and 23S rDNA were amplified using primers S-D-Bact-1494-a-S-20 and L-D-Bact-0035-a-A-15 as previously described (Daffonchio et al, 1998), except that primer S-D-Bact-1494-a-S-20 was 5 end labelled with the phosphoramidite dye 5-FAM. Aliquots of the PCR products (1 to 5 µL) were mixed with 1 µL of the GeneScan-1000 [ROX] internal size standard (Applied Biosystems), 20 µL of deionized formamide was added, the mixture was denatured at 95 • C for 5 min and cooled in an ice bath.…”
Section: Molecular Analysis Of the Rhizosphere Bacterial Community Bymentioning
confidence: 99%
“…); and (iii) direct electrophoresis of PCR products. In the latter group, some techniques are based on ribosomal DNA spacers [1][2][3][4] and the results obtained have shown that, for most species, the PCR patterns are specific. Also, the existence of repetitive sequences in the bacterial genome has been widely used for typing bacteria, obtaining PCR patterns by direct electrophoresis of the PCR products generated.…”
mentioning
confidence: 99%
“…Additional PCR was carried out with specific primers in order to identify the presence of cry1Aa, cry1Ab, cry1Ac, cry1Ad, cry2Aa, cry2Ab and cry2Ac genes (Ben-Dov et al 1997;Bravo et al 1998). ITS-PCR was performed as previously described by Daffonchio et al (1998).…”
Section: Dna Preparation and Pcr Amplificationmentioning
confidence: 99%